Analiza projektów studenckich dotyczących pracy dydaktycznej z uczniami o specjalnych potrzebach edukacyjnych w klasie włączającej i zdigitalizowanym środowisku – odpowiedź na czasy pandemii COVID-19 - Król-Gierat, Werona; Rak, Katarzyna (Neofilolog, 2022)
The 2020/21 academic year proved to be unprecedented in many ways for students and lecturers alike. The need to move from traditional education to a virtual classroom during the Covid-19 pandemic became a stimulus to seek new ways to work and expand knowledge. The aim of this paper is to present the outcome of project work completed by university students of a teaching specialization, which included ways of teaching and ICT tools suitable for working with learners with Special Educational Needs (SEN) in a traditional classroom and in a digital environment. With the increase in remote learning, the challenge of meeting the needs of learners with SEN is considerable. Therefore, inclusive classrooms should be designed with remote learning in mind, so that the teachers are ready to substitute or enrich traditional resources with educational technologies. With the right solutions, teachers can innovate and redefine their classrooms, remodelling them into a mix of face-to face and online delivery. However, different categories of SEN require different solutions. The analysis of the projects confirms that when students are involved in problem-solving and focusing on solutions, they learn more about how to contribute to effective learning in a meaningful way.